Badania zachowań negocjacyjnych w krajach Unii Europejskiej - aspekt kulturowy - Kałążna-Drewińska, Urszula (The Study of Various Types of Behaviour During Negotiations in the European Union Countries - Cultural Aspects, 2006)
The framework of the paper's contents is as follows:1. Cultural conditioning of behaviours during negotiations.2. Methodological basis of inter-cultural studies of behaviours during negotiations.3. Similarities and differences in behaviours during negotiations as exhibited the representatives of the European Union countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 214-222